PELAKSANAAN PELAYANAN PERIJINAN SATU PINTU PADA KANTOR PELAYANAN PERIJINAN TERPADU DI KABUPATEN SEMARANG (PELAYANAN SURAT IJIN USAHA PERDAGANGAN) - Soebandriyo Soebandriyo; Slamet Slamet (JURNAL LITBANG PROVINSI JAWA TENGAH, 2010)
This research locations in the district of Semarang, the research objectives: To identify problems in the implementation procedures of service trade business license issuance at the Office of Licensing Services Integrated Semarang District, To overcome the problems in the implementation of the issuance of Permit Trading in the Integrated Licensing Office Regency Semarang, properties descriptive research, qualitative research informants licensing officers and the applicant. In conclusion, the existing problems include: incomplete requirements, but applicants forced to calculate the completion time permitting SIUP. calculated starting from the intake form, lack of socialization to the community about the requirements to obtain SIUP, who signed SIUP If there is a sudden event invited the meeting, to sign SIUP experiencing delays, lack of facilities and infrastructure, especially the chair, Lack of Human Resources. How to solve the problem through: Approaches to the applicant's licensing terms were eventually SIUP with the applicant willing to accept, with or brusur lifet made containing about application requirements and period of completion SIUP provided or distributed to the applicant, before the leadership left the office to sign blank SIUP first, With the addition of seats, upgrading of human resources.